Cold low pressure O2 plasma treatment of Crocus sativus: An efficient way to eliminate toxicogenic fungi with minor effect on molecular and cellular properties of saffron. (15th August 2018) - Hosseini, Seyed Iman; Farrokhi, Naser; Shokri, Khadijeh; Khani, Mohammad Reza; Shokri, Babak
Highlights: 60 W and 15 min O2 plasma completely eradicated Aspergillus load of saffron. O2 plasma treatment slightly decreased the antioxidant activity of treated saffron. No considerable changes were evident on crocin, picrocrocin, safranal of saffron. O2 plasma treatment has no considerable effect on saffron color, odor and flavor. Abstract: In this study cold low pressure radiofrequency oxygen plasma was used for the first time to inactivate toxicogenic fungi proliferation on saffron. Varieties of plasma produced reactive oxygen species which were investigated by optical emission spectroscopy. The data were indicative of the absence of UV radiation. Effects of plasma treatment on antioxidant activity, metabolic content, colour, odour and flavour parameters and physical impact on saffron were investigated. A range of plasma powers and exposure times were assayed in suppression of fungal growth. Amongst which power of 60 W for 15 min was used to eradicate Aspergillus and other microorganisms. The ferric reducing antioxidant power was changed from 1778.21 to 1674.25 mM/g dry weight following plasma treatment. Moreover, crocin ester, picrocrocin and safranal metabolites reduced insignificantly. Additionally, plasma had no significant impact on colour, odour and flavour of saffron.